Reformist-Modernist Ideology in Indonesian Qur’anic Exegesis: A Sociology of Knowledge Analysis of Hasbi ash-Shiddieqy’s Tafsir an-Nuur - Saddad, Ahmad; Aziz, Thoriqul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2026)
This study examines the reformist-modernist Islamic ideology embedded in Tafsir al-Qur’an al-Majid an-Nuur by Teungku Muhammad Hasbi ash-Shiddieqy (1904–1975), one of the most influential Indonesian mufassir of the twentieth century. The study departs from the argument that Qur’anic exegesis in Indonesia has long been shaped by ideological contestation between reformist-modernist and traditionalist Muslim orientations, yet the ideological structure of individual tafsir works remains insufficiently explored. Employing a qualitative descriptive-analytical method and Karl Mannheim’s sociology of knowledge as the theoretical framework, this research analyzes Tafsir an-Nuur as the primary source alongside biographical, historical, and socio-political data related to Hasbi’s intellectual life. The findings reveal three major points. First, Hasbi’s reformist-modernist ideology is reflected in his consistent call to return to the Qur’an and the Sunnah and in his efforts to purify Islamic teachings through criticism of taqlid, bid‘ah, khurāfāt, and tawassul practices considered inconsistent with authentic Islam. Second, his tafsir was shaped by several socio-historical factors, including the dominance of traditionalist Muslim communities in Indonesia, his political involvement in the reformist-oriented Masyumi Party, and the persistence of syncretic cultural traditions rooted in pre-Islamic beliefs. Third, Tafsir an-Nuur significantly influenced reformist Muslim communities, particularly Muhammadiyah, while also contributing to the development of contextual and socially engaged Qur’anic exegesis in Indonesia. This study contributes to Indonesian tafsir studies by demonstrating the dialectical relationship between ideology, socio-political context, and Qur’anic interpretation, while also extending Mannheim’s sociology of knowledge into the study of modern Indonesian tafsir. Penelitian ini mengkaji ideologi Islam reformis-modernis yang terkandung dalam *Tafsir al-Qur’an al-Majid an-Nuur* karya Teungku Muhammad Hasbi ash-Shiddieqy (1904–1975), salah satu mufassir Indonesia paling berpengaruh pada abad ke-20. Penelitian ini berangkat dari argumen bahwa tafsir Al-Qur’an di Indonesia sejak lama dibentuk oleh kontestasi ideologis antara orientasi Islam reformis-modernis dan tradisionalis, namun struktur ideologis dari karya tafsir individual masih jarang dikaji secara mendalam. Dengan menggunakan metode kualitatif deskriptif-analitis dan kerangka sosiologi pengetahuan Karl Mannheim, penelitian ini menganalisis *Tafsir an-Nuur* sebagai sumber utama yang dipadukan dengan data biografis, historis, dan sosial-politik terkait kehidupan intelektual Hasbi. Hasil penelitian menunjukkan tiga temuan utama. Pertama, ideologi reformis-modernis Hasbi tercermin dalam seruannya untuk kembali kepada Al-Qur’an dan Sunnah serta upayanya memurnikan ajaran Islam melalui kritik terhadap taqlid, bid‘ah, khurāfāt, dan praktik tawassul yang dianggap tidak sesuai dengan Islam autentik. Kedua, tafsir Hasbi dipengaruhi oleh beberapa faktor sosio-historis, antara lain dominasi masyarakat Muslim tradisionalis di Indonesia, keterlibatannya dalam Partai Masyumi yang berorientasi reformis, serta kuatnya tradisi sinkretik yang berakar pada kepercayaan pra-Islam. Ketiga, *Tafsir an-Nuur* memberikan pengaruh signifikan terhadap komunitas Muslim reformis, khususnya Muhammadiyah, sekaligus berkontribusi pada perkembangan tafsir Al-Qur’an yang kontekstual dan responsif terhadap realitas sosial di Indonesia. Penelitian ini berkontribusi pada studi tafsir Indonesia dengan menunjukkan hubungan dialektis antara ideologi, konteks sosial-politik, dan interpretasi Al-Qur’an, sekaligus memperluas penerapan sosiologi pengetahuan Karl Mannheim dalam kajian tafsir modern Indonesia.